Composition variability of the organic fraction of municipal solid waste and effects on hydrogen and methane production potentials. (February 2015) - Alibardi, Luca; Cossu, Raffaello
Highlights: OFMSW waste composition variability was defined over time. Hydrogen potential productions of OFMSW depend by waste composition. Hydrogen yields of OFMSW mixtures depend largely on carbohydrate content. OFMSW waste composition is essential to compare results on hydrogen production. Abstract: The composition of the Organic Fraction of Municipal Solid Waste (OFMSW) strongly depends on the place and time of collection for a specific municipality or area. Moreover synthetic food waste or organic waste from cafeterias and restaurants may not be representative of the overall OFMSW received at treatment facilities for source-separated waste. This work is aimed at evaluating the composition variability of OFMSW, the potential productions of hydrogen and methane from specific organic waste fractions typically present in MSW and the effects of waste composition on overall hydrogen and methane yields. The organic waste fractions considered in the study were: bread–pasta, vegetables, fruits, meat–fish–cheese and undersieve 20 mm. Composition analyses were conducted on samples of OFMSW that were source segregated at household level. Batch tests for hydrogen and methane productions were carried out under mesophilic conditions on selected fractions and OFMSW samples. Results indicated that the highest production of hydrogen was achieved by the bread–pasta fraction while the lowest productions were measured for the meat–fish–cheese fraction. The results indicated that the content of these two fractions in organic waste had a direct influence on the hydrogen production potentials of OFMSW. The higher the content of bread–pasta fraction, the higher the hydrogen yields were while the contrary was observed for the meat–fish–cheese fraction. The definition of waste composition therefore represents fundamental information to be reported in scientific literature to allow data comparison. The variability of OFMSW and its effects on hydrogen potentials might also represents a problematic issue in the management of pilot or full-scale plants for the production of hydrogen by dark fermentation.